1989
DOI: 10.1021/bi00430a051
|View full text |Cite
|
Sign up to set email alerts
|

Calcitroic acid, end product of renal metabolism of 1,25-dihydroxyvitamin D3 through the C-24 oxidation pathway

Abstract: About a decade ago calcitroic acid was isolated as a major side chain cleaved water-soluble metabolite of 1,25-dihydroxyvitamin D3 [Esvelt, R. P., Schnoes, H. K., & Decula, H. F. (1979) Biochemistry 18, 3977]. Presently, calcitroic acid is being considered as the major excretory form of 1,25-dihydroxyvitamin D3. However, the exact site or sites of calcitroic acid production and the possible side chain modified intermediary metabolites that may be formed during the conversion of 1,25-dihydroxyvitamin D3 into ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
128
0
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 229 publications
(132 citation statements)
references
References 23 publications
3
128
0
1
Order By: Relevance
“…This 24-hydroxylation is thought to be the first step in the catabolic pathway (2,3). In vivo studies have shown that the 24-hydroxylase is induced by 1,25-(OH)2D3 (4), essentially inducing its own inactivation.…”
mentioning
confidence: 99%
“…This 24-hydroxylation is thought to be the first step in the catabolic pathway (2,3). In vivo studies have shown that the 24-hydroxylase is induced by 1,25-(OH)2D3 (4), essentially inducing its own inactivation.…”
mentioning
confidence: 99%
“…Finally, after side chain cleavage, calcitroic acid is formed. Calcitroic acid is then excreted into the bile (Makin et al, 1989;Reddy and Tserng, 1989;Zimmerman et al, 2001). The expression of both the activating (25-and 1-hydroxylases) and the catabolizing (24-hydroxylase) enzymes by cells of certain tissues, indicates that the multifunctional hormone 1,25-dihydroxyvitamin D 3 can be produced locally in some tissues, including cells in the skin, breast, colon, prostate, lung, and various cells of the immune system.…”
Section: Vitamin D Is Activated To a Multifunctional Hormone With Effmentioning
confidence: 99%
“…Work in our laboratory [7] demonstrating the existence of a C23-alcohol derived from 25-OH-D3 strengthened the theory that calcitroic acid was derived from the C-24 oxidation pathway. Recently two groups [8,9] have achieved the generation of calcitroic acid from 1,25-(OH)2D3 using in vitro models of kidney and bone. Figure 1 illustrates our current concept of the steps involved in this pathway.…”
Section: Introductionmentioning
confidence: 99%